Analyzing excess mortality from cancer among individuals with mental illness. Issue 13 (12th April 2013) - Musuuza, Jackson S.; Sherman, Marion E.; Knudsen, Kraig J.; Sweeney, Helen Anne; Tyler, Carl V.; Koroukian, Siran M.
<x xml:space="preserve">Abstract</x> BACKGROUND The objective was to compare patterns of site‐specific cancer mortality in a population of individuals with and without mental illness. METHODS This was a cross‐sectional, population‐based study using a linked data set comprised of death certificate data for the state of Ohio for the years 2004‐2007 and data from the publicly funded mental health system in Ohio. Decedents with mental illness were those identified concomitantly in both data sets. We used age‐adjusted standardized mortality ratios (SMRs) in race‐ and sex‐specific person‐year strata to estimate excess deaths for each of the anatomic cancer sites. RESULTS Overall, there was excess mortality from cancer associated with having mental illness in all the race/sex strata: SMR, 2.16 (95% CI, 1.85‐2.50) for black men; 2.63 (2.31‐2.98) for black women; 3.89 (3.61‐4.19) for nonblack men; and 3.34 (3.13‐3.57) for nonblack women. In all the race/sex strata except for black women, the highest SMR was observed for laryngeal cancer, 3.94 (1.45‐8.75) in black men and 6.51 (3.86‐10.35) and 6.87 (3.01‐13.60) in nonblack men and women, respectively. The next highest SMRs were noted for hepatobiliary cancer and cancer of the urinary tract in all race/sex strata, except for black men. CONCLUSIONS Compared with the general population in Ohio, individuals with mental illness experienced excess mortality from most cancers, possibly explained by a higher prevalence of smoking, substance abuse, and chronic hepatitis B or C infections in individuals with mental illness. Excess mortality could also reflect late‐stage diagnosis and receipt of inadequate treatment. Cancer 2013;119:2469‐2476. © 2013 American Cancer Society.